Inclusion in the city : selection, schooling and community - Potts, Patricia (RoutledgeFalmer, 2003)
This volume explores inclusion and exclusion in the context of policy and practice in Birmingham. Detailed case studies, based on research specially undertaken for this book, relate inclusion to key issues in contemporary education.